Post a New Question

Algebra

posted by .

((k^2+6k+9)/(k^2+12k+27))×(k^2+9)/((k^2+12k+27))
express in lowest terms

  • Algebra -

    k ^ 2 + 6 k + 9 = ( x + 3 ) * ( x + 3 )



    k ^ 2 + 12 k + 27 = ( x + 9 ) * ( x + 3 )


    ((k^2+6k+9)/(k+9)*(k+3)))*(k^2+9)/((k^2+12k+27))=

    ((k+3)*(k+3))/((x+9)*(k+3)) * ((k^2+9)/(((x+9)*(k+3))=

    ((k+3))/((x+9)) * ((k^2+9)/(((x+9)*(k+3))=

    (k^2+9)/((x+9)*(k+9))=

    (k^2+9)/(x+9)^2

  • Algebra -

    (k^2+9)/((k+9)*(k+9))=

    (k^2+9)/(k+9)^

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question